Energy Metabolism in Cardiac Remodeling and Heart Failure - Gaiolla, Paula Schmidt Azevedo [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Santos, Priscila P. [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP] (Wolters Kluwer, 2013)
Fatty acids are the main substrates used by mitochondria to provide myocardial energy under normal conditions. During heart remodeling, however, the fuel preference switches to glucose. In the earlier stages of cardiac remodeling, changes in energy metabolism are considered crucial to protect the heart from irreversible damage. Furthermore, low fatty acid oxidation and the stimulus for glycolytic pathway lead to lipotoxicity, acidosis, and low adenosine triphosphate production. While myocardial function is directly associated with energy metabolism, the metabolic pathways could be potential targets for therapy in heart failure. © 2013 by Lippincott Williams & Wilkins.
Keywords: β-oxidation; cardiac failure; energy metabolism; glycolysis; heart remodeling; mitochondrial dysfunction; adenosine triphosphate; glucose transporter 1; glucose transporter 4; lactate dehydrogenase; protein kinase B; ranolazine; bioavailability; carbohydrate metabolism; cell damage; citric acid cycle; energy yield; esterification; fatty acid oxidation; glucose oxidation; glucose transport; heart failure; heart function; heart muscle metabolism; heart ventricle remodeling; human; lipid storage; lipotoxicity; metabolism; mitochondrial dynamics; mitochondrial membrane; oxidative phosphorylation; oxidative stress; oxygen consumption; protein dephosphorylation; respiratory chain; review; sarcoplasmic reticulum; upregulation; Adenosine Triphosphate; Chronic Disease; Energy Metabolism; Heart; Heart Failure; Humans; Mitochondria, Heart; Mitochondrial Diseases; Myocardium; Nitric Oxide; Oxidation-Reduction